Ecological research and environmental management: We need different interfaces based on different knowledge types. (15th July 2018) - Gosselin, Frédéric; Cordonnier, Thomas; Bilger, Isabelle; Jappiot, Marielle; Chauvin, Christophe; Gosselin, Marion
Abstract: The role of ecological science in environmental management has been discussed by many authors who recognize that there is a persistent gap between ecological science and environmental management. Here we develop theory through different perspectives based on knowledge types, research categories and research–management interface types, which we combine into a common framework. To draw out insights for bridging this gap, we build our case by: (i) explicitizing the link between three categories of ecological research and the type of research–management interface they are associated with. We first evaluate three types of unidirectional interfaces and recommend a new kind of interface – called the Research-Within-Management interface (RWM). (ii) suggesting that adaptive management and structured decision-making can integrate all these different angles and serve as meta-interfaces in their relation to research. (iii) distinguishing explanatory knowledge from empirical knowledge, and contending that explanatory knowledge is not necessarily the most important output for the research-management interface today. (iv) highlighting that experiential ecological knowledge—including the expertise and experience of managers, citizens and scientists—is another primary knowledge input in environmental decision-making that should not be systematically downplayed. We point out the complementarities as well as the specificities and limitations of the different types of ecological research, ecological knowledge and research–management interfaces, which is of major importance for environmental management and research policies. Graphical abstract: Image 1 Highlights: We reconcile different perspectives on ecological research-management interfaces. Different types of interfaces and different types of ecological knowledge are needed. We propose a new Research-Within-Management interface (RWM). Adaptive management is a promising meta-interface.